Molecular characterization of rotavirus genotypes in immunosuppressed and non-immunosuppressed pediatric patients - Luciane A. Pereira; Carla E.O. Ferreira; Giovana D. Turchetto; Meri B. Nogueira; Luine R. Vidal; Cristina R. Cruz; Maria C. Debur; Sergio M. De Almeida; Sonia M. Raboni (Brazilian Society of Pediatrics, 2013)
Objective: To describe the genotypic variability of group A rotavirus (RVA) found in immunosuppressed and non-immunosuppressed pediatric patients treated at the Hospital de Clínicas da Universidade Federal do Paraná (HC-UFPR), Curitiba, Paraná. Methods: A cross-sectional study was conducted with 1,140 stool samples collected from April, 2001 to December, 2008 in outpatients and hospitalized patients with acute gastroenteritis referred to the hospital. RVA diagnosis was performed through the latex agglutination method and enzyme immunoassay. Reverse transcription followed by multiplex hemi-nested polymerase chain reaction (PCR) and nucleotide sequencing were used for genotype characterization. Genotype combinations, clinical data, epidemiological data, laboratory data, and presence of hospital-acquired infections were reported. Results: A total of 80 rotavirus-positive stool samples were analyzed. The most frequent associations between genotypes G and P were: G4 P[8] (38.9%), G1 P[8] (30.5%), G9 P[8] (13.9%), G2 P[4] (6.9%), and G3 P[8] (1.4%). G2 P[4] was the most prevalent genotype after the vaccine implementation in the years 2006 and 2008. A total of 62.5% of children aged less than 12 months were found to be infected. Of these, 55.6% had severe dehydration and 26.7% needed intensive care. A frequency of 12.5% of nosocomial infections was found. No correlation was observed between genotype and severity of infection in the study patients. Conclusion: RVA infections can be associated with severe clinical manifestations, and the surveillance of genotypic variability of this virus is crucial to monitor the emergence of new strains and the impact of the immunization in these patients.